(untitled) (Cultura Económica, 2018)
The author presents the central arguments developed by both Höffe and Luhmann regarding the foundations of an institutional normative order to ensure political and non-metaphysical justice. Thus, presents the contributions of both philosophers; in the first section, he explains the Luhmanian ethics, and afterwards describes the criticism of Höffe to Luhmannian positivism. Finally, the author highlights the contributions of Luhmann and Höffe and statuses them as the most important ideas in recent decades in philosophy of German law.